Subcellular location of source proteins improves prediction of neoantigens for immunotherapy. (31st October 2022) - Castro, Andrea; Kaabinejadian, Saghar; Yari, Hooman; Hildebrand, William; Zanetti, Maurizio; Carter, Hannah
Abstract: Antigen presentation via the major histocompatibility complex (MHC) is essential for anti‐tumor immunity. However, the rules that determine which tumor‐derived peptides will be immunogenic are still incompletely understood. Here, we investigated whether constraints on peptide accessibility to the MHC due to protein subcellular location are associated with peptide immunogenicity potential. Analyzing over 380, 000 peptides from studies of MHC presentation and peptide immunogenicity, we find clear spatial biases in both eluted and immunogenic peptides. We find that including parent protein location improves the prediction of peptide immunogenicity in multiple datasets. In human immunotherapy cohorts, the location was associated with a neoantigen vaccination response, and immune checkpoint blockade responders generally had a higher burden of neopeptides from accessible locations. We conclude that protein subcellular location adds important information for optimizing cancer immunotherapies. Synopsis: Predicting which peptides can serve as neoantigens targeted by anti‐tumor immunity remains difficult. Here, the subcellular location of peptide source proteins is found to affect major histocompatibility complex (MHC) elution and improve immunogenicity prediction. Peptides eluted from MHC I and MHC II molecules reflect biases in the subcellular location of the parent proteins An embedding‐based indicator of parent protein location improves the prediction of neoepitope immunogenicity and response to immune checkpoint blockade Neoepitope location improves the estimation of effective neoantigen burden and stratification of patients with potential response to immunotherapy Abstract : Large‐scale analyses of peptide immunogenicity reveal that the inclusion of parent protein location improves prediction potential.